2016
DOI: 10.18632/oncotarget.13326
|View full text |Cite
|
Sign up to set email alerts
|

The chromatin-remodeling enzyme BRG1 promotes colon cancer progression via positive regulation of WNT3A

Abstract: In this study, we aimed to elucidate the clinical significance and underlying mechanisms of BRG1 in colon cancer. In the clinical analysis, overexpression of BRG1 correlates with colon cancer progression in two cohorts (n = 191 and n = 75). Kaplan-Meier survival analysis revealed that BRG1 is a prognosis predictor for overall survival (P < 0.001) and disease-free survival (P = 0.001). Knocking down BRG1 expression significantly suppressed the proliferation and invasion in colon cancer cells. The expression pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 38 publications
2
24
0
Order By: Relevance
“…6 ). ALDOA is a glycolytic enzyme observed to accumulate in CRC 38 , COPS6 is a subunit of the COP9 signalosome specifically required to drive CRC 39 41 , MCM2 functions as a DNA replication licensing factor needed to override once-per-cycle DNA replication in S-phase 42 , 43 and SMARCA4 (BRG1) is a SWI/SNF component activating WNT and VEGF signaling to drive CRC 31 , 44 , 45 . While HLA peptides from these four proteins were reliably detected on normal colon organoids, these were consistently absent from the ligandome of all four CRC organoid lines, suggesting that these proteins may be functionally important in CRC and therefore preserved from degradation (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6 ). ALDOA is a glycolytic enzyme observed to accumulate in CRC 38 , COPS6 is a subunit of the COP9 signalosome specifically required to drive CRC 39 41 , MCM2 functions as a DNA replication licensing factor needed to override once-per-cycle DNA replication in S-phase 42 , 43 and SMARCA4 (BRG1) is a SWI/SNF component activating WNT and VEGF signaling to drive CRC 31 , 44 , 45 . While HLA peptides from these four proteins were reliably detected on normal colon organoids, these were consistently absent from the ligandome of all four CRC organoid lines, suggesting that these proteins may be functionally important in CRC and therefore preserved from degradation (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This finding provides additional evidence that elevated BRG1 expression, not BRG1 mutation, is a marker for poor prognosis in an increasing number of cancer types. Prior work has demonstrated that high BRG1 mRNA expression inversely correlates with patient survival in breast cancer (27,28,39), colorectal cancer (62,63), and neuroblastoma (29). In addition, BRG1 is required for various aspects of cancer cell survival, proliferation, and function in HeLa cells (64), leukemia cells (65,66), breast cancer (33,43), hepatocarcinoma (67), colorectal cancer (68), neuroblastoma (29), melanoma (30,69,70), and certain medullablastoma tumors (71).…”
Section: Discussionmentioning
confidence: 99%
“…In a clinical analysis of colon cancer, BRG1 expression levels were positively correlated with cancer progression and negatively correlated with patient survival. Reduction of BRG1 levels resulted in reduced cell proliferation in culture and reduced tumor growth in orthotopic transplants [ 99 ]. Prior studies had implicated WNT3A as a regulator of colon cancer cells [ 100 ].…”
Section: Brg1 Is Expressed At Elevated Levels In Other Tumor Typesmentioning
confidence: 99%